Factors associated with voice disorders among teachers: a case-control study - Giannini,Susana Pimentel Pinto (2013)
Purpose: We aimed at verifying an association between voice disorders/stress and loss of work ability among female teachers who work in São Paulo's public school system. Methods: This is a paired case– control study. The case group was composed offiteachers with alterations in speech and larynges assessments, and the control group was formed by teachers without alterations in these evaluations who work in the same schools. Both groups answered the following questionnaires: Conditions of Vocal Production—Teachers, Job Stress Scale, and Work Ability Index. The analysis was performed using the chi-square association test and logistic regression models with the purpose of estimating the association between independent variables and voice disorders. Results: We found differences between the groups in relation to stress in the workplace under high demand, a situation that poses greater risks of adverse reactions to the workers' physical and mental health. Regarding the ability to work, the categories poor and moderate ability for work are associated with voice disorders, regardless of job stress factors, age, and the unsatisfactory acoustic properties of the classrooms. Conclusion: This study confirmed the association between voice disorders and job stress, as well as between voice disorders and loss of work ability.